Risk of gastrointestinal complications in breast cancer patients treated with neratinib: a meta-analysis. Issue 10 (3rd October 2017) - Jiang, Nan; Song, Xiang-Wei; Lin, Jing-Jing; Wang, Zhan-Yu; Zhang, Bei-Ning; Li, Ao; Yan, Ru-Yi; Yan, Hong-feng; Fu, Xiao- Yan; Zhou, Jin-Lian; Li, Cheng-Lin; Cui, Yan
ABSTRACT: Backgrounds : Neratinib is a potent EGFR/HER2 kinase inhibitor. Gastrointestinal complications (i.e. diarrhea, vomiting and nausea) are the most common adverse events. In this study, we aimed to investigate (1) the overall incidence and relative risk (RR) of diarrhea, vomiting and nausea and (2) whether combination neratinib therapy increased the incidence of gastrointestinal complications versus neratinib alone. Methods : Relevant studies were identified from the PubMed database, from abstracts presented at the American Society of Clinical Oncology annual conference and from the Web of Science database. Incidences, RRs, and 95% confidence intervals (CIs) were calculated. Results : The incidences of all-grade diarrhea, vomiting and nausea in the neratinib groups were 89% (95% CI = 77–95%), 31% (95% CI = 25–37%) and 44% (95% CI = 33–55%), respectively. The neratinib arms significantly increased the risk of diarrhea and vomiting in comparison with the control groups (diarrhea: all-grade, RR = 2.06, 95% CI = 1.38–3.08, P = 0.0004; grade 3/4, RR = 8.77, 95% CI = 2.91–26.40, P = 0.0001; vomiting: all-grade, RR = 2.02, 95% CI = 1.10–3.71, P = 0.02; grade 3/4, RR = 7.10, 95% CI = 3.33–15.15, P < 0.00001). Conclusions : Our meta-analysis demonstrates that the neratinib arms are associated with a significantly increased risk of diarrhea and vomiting.